Aspects of Asperger's : Success in the Teens and Twenties. - Brown, Maude (Lucky Duck Books., 2004)
"Once I started this book I was hooked. Where was this book 10 years ago? So many of the problems I have dealt with and worked out through triall and error are here. It would have saved many tears and tantrums - and those not just from me! Once purchased, you will use it over and over again, for reference"--Communication A thought provoking and practical book about how one supporter, a grandmother, helped her granddaughter search for ways to help her overcome the difficulties they both faced. This book does not dwell on the problems but instead looks.